2018
DOI: 10.1371/journal.pone.0207306
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of concomitant acromioplasty in the treatment of rotator cuff tears: A systematic review and meta-analysis

Abstract: BackgroundScientific evidence is not clear regarding the routine use of acromioplasty in the treatment of rotator cuff repair. The aim of this study was to compare clinical outcomes between patients undergoing arthroscopic rotator cuff repair with and without concomitant acromioplasty.MethodsMedline, Cochrane Library, and EMBASE databases were searched to identify eligible studies focused on arthroscopic rotator cuff repair with and without acromioplasty from January 2000 to February 2018. Postoperative functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Rotator cuff reconstruction may be accompanied by acromioplasty ( 25 ) . Evidence of higher risk for complete supraspinatus tendon rupture in patients with acromial inferolateral tilt accentuation may influence the orthopedists to associate acromioplasty to the reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Rotator cuff reconstruction may be accompanied by acromioplasty ( 25 ) . Evidence of higher risk for complete supraspinatus tendon rupture in patients with acromial inferolateral tilt accentuation may influence the orthopedists to associate acromioplasty to the reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…However, an acromial bone spur and rotator cuff tear may not have a causeand-effect relationship but be normal age-related changes. Acromioplasty (removal of bone spurs) is not superior to an exercise programme without surgery or a placebo acromioplasty (Cheng et al, 2018;Lähdeoja et al, 2020;Lewis, 2016Lewis, , 2018Lewis, 2009a;Sun et al, 2018).…”
Section: Reduction In the Subacromial Space Distancementioning
confidence: 99%
“…Over the past 10 years, multiple Level-I and II systematic reviews and meta-analyses 2-4 as well as randomized controlled trials 5 have shown no difference in patient-reported outcomes or retear rates with follow-up of <8 years. Most of these studies had follow-up of 2 years and demonstrated no significant difference in the need for reoperation.…”
Section: Commentarymentioning
confidence: 99%